Marine water quality index trend from eight-year study of Klang Estuary - Samsudin, Mohd Saiful; Azid, Azman; Yunus, Kamaruzzaman (Innovative Scientific Information & Services Network, 2019)
In the context of marine water quality monitoring, detailed information concerning the marine water quality index is importance. The paper presents the analysis of 8-year period trend (2010-2017) marine water quality index and the other marine water quality parameters fluctuations in the Klang estuary, which is have the famous Port Klang, the one of the largest and busiest ports in peninsular Malaysia. The 2010–2017 data employed in this study entailed 12 marine water quality parameters. In order to investigate the trend analysis, the nonparametric Mann-Kendall statistical test has been used. The result shows the upward trends for MWQI, Salinity, COND, TEMP, DO and O&G and downward trends for pH, TUR, TSS, coliform, PO4, NH3N and NO3. in 8-year period in Klang estuary. The results indicated Klang Estuary has experienced a mild pollution trend due to anthropogenic influence from domestic activities in the vicinity of the estuary.